Colors and Handles: How Action Primes Perception - Costantini, Marcello; Quarona, Davide; Sinigaglia, Corrado (Frontiers in Human Neuroscience, 2021)
How do deeply action influence perception? Does action performance affect the perception of object features directly related to action only? Or does it concern also object features such as colors, which are not held to directly afford action? Answering these questions was the main aim of the present study. Participants were asked to repeatedly reach for and grasp a handled mug hidden to their view before judging whether a visually presented mug was blue rather than cyan. The motor training impacted on their perceptual judgments, by fastening participants’ responses, when the presented mug was oriented congruently with the trained hand. This priming effect did not occur when the motor training consisted in repeatedly reaching for and touching the mug with the hand closed in a fist. This indicates that action performance may shape the perceptual judgment on object features, even when these features are colors and do not afford any action How we act on the surrounding objects is therefore not without consequence for how we experience them.